Peningkatan Hasil Belajar Siswa Pada Pembelajaran Tematik Terpadu Menggunakan Pendekatan Contextual Teaching and Learning - Nadhira, Nadhira; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to describe the increase in student learning outcomes in integrated thematic learning using Contaxtual Teaching and Learning approach in class IV SD Pembangunan Laboratorium UNP . The research subjects were teachers (practitioners) and 27 students. The research location is SD Pembangunan Laboratorium UNP. The results showed an increase in: a) RPP observation of the first cycle was 81,95% (B), the second cycle was 94,4% (A); b) Observation teachers aspect of the first cycle is 73,75% (C), the second cycle is 92,5% (A); c) Observation students aspect of the  first cycle is 71,23%  (C) and the second cycle is 92,5% (A); d) learning outcomes in the first cycle are 70,06 (C) and the second cycle are 86,83 (B).